Die Welt des Michael Ende - Ende, Michael,Hocke, Roman,Hoffmann, Markus,Hübschmann, Ulrike,Wick, Steffen (Steinbach, 2009)
Bekannt wurde Michael Ende vor allem als Autor der fantastischen Erzählung
9783886984688
Keywords: CD